Model behavior animal experiments, complexity, and the genetics of psychiatric disorders - Nelson, Nicole C. (The University of Chicago Press, 2018)
Mice are used as model organisms across a wide range of fields in science today-but it is far from obvious how studying a mouse in a maze can help us understand human problems like alcoholism or anxiety. How do scientists convince funders, fellow scientists, the general public, and even themselves that animal experiments are a good way of producing knowledge about the genetics of human behavior? Nicole C. Nelson takes us inside an animal behavior genetics laboratory to examine how scientists create and manage the foundational knowledge of their field.